Implementation of Guidance and Counseling Services in the Independent Curriculum High Schools - Kamaruzzaman; Rustam; Luhur Wicaksono; Nini; Irena Cahayani (G-Couns: Jurnal Bimbingan dan Konseling, 2025)
A comprehensive guidance and counselling service manager is included in the curriculum. Independence is a skill that BK teachers must possess. This study aims to determine the Implementation of Comprehensive Guidance and counselling services in the Independent Curriculum in Pontianak City High Schools in 2024. The method used is descriptive with a Subick survey research form. This is a Pontianak City High School that has implemented the Independent Curriculum. The research instruments used are interview guides and questionnaires. The results of the study contain a description of comprehensive guidance and counselling services in the implementation of the independent curriculum, where the implementation of guidance and counselling services in Pontianak City High Schools has been running well, although some need to be improved. The rules regarding the suitability of service programs, the programming of development activities, and the distribution of the number of BK teachers according to the number of students indicate room for improvement in evaluating original programs and compiling service programs, BK, by the Independent Curriculum. Keywords: comprehensive guidance and counselling, independent curriculum, counselling